2023
DOI: 10.3390/met13030525
|View full text |Cite
|
Sign up to set email alerts
|

Twinning in Hexagonal Close-Packed Materials: The Role of Phase Transformation

Abstract: Twinning is a major mechanism of plastic deformation in hexagonal close-packed (hcp) structures. However, a mechanistic understanding of twin nucleation and growth has yet to be established. This paper reviews the recent progress in the understanding of twinning in hcp materials—particularly the newly discovered phase transformation-mediated twinning mechanisms—in terms of crystallographical analysis, theoretical mechanics calculations, and numerical simulations. Moreover, the relationship between phase transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 105 publications
0
4
0
Order By: Relevance
“…At higher magnifications ( Figure 3 a), it can be clearly seen that large α′-platelets can be considered as a colony of alternating α′-lamellae of the same orientation, morphologically resembling annealing twins. Crystallographic analysis revealed that some of these platelets are characterized by a misorientation angle of ~60° around the a α -axis and can be classified as { }-compression twins [ 49 ]. The rest of the plates in the same colony are characterized by ~85° misorientation around the a α -axis with its neighbors and can be classified as { }-tension twins [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…At higher magnifications ( Figure 3 a), it can be clearly seen that large α′-platelets can be considered as a colony of alternating α′-lamellae of the same orientation, morphologically resembling annealing twins. Crystallographic analysis revealed that some of these platelets are characterized by a misorientation angle of ~60° around the a α -axis and can be classified as { }-compression twins [ 49 ]. The rest of the plates in the same colony are characterized by ~85° misorientation around the a α -axis with its neighbors and can be classified as { }-tension twins [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Crystallographic analysis revealed that some of these platelets are characterized by a misorientation angle of ~60° around the a α -axis and can be classified as { }-compression twins [ 49 ]. The rest of the plates in the same colony are characterized by ~85° misorientation around the a α -axis with its neighbors and can be classified as { }-tension twins [ 49 ]. Thus, α′-colonies consisting of relatively large alternating α′-platelets with twin misorientations were formed during cooling between the β-transus and the temperature of the invariant transformation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations